Effects of combined exposure to heavy metals on lower respiratory flora and its role of lung injury in rats - Ping Ding; Xiaoxia Wang; Nan Li; Shuxia Yu; Shuxia Yu; Yiwen Zhang; Junpu Yu; Tian Tian; Rentong Chen; Bin Luo; Li Ma; Rongxuan Zhang; et al. (Frontiers in Microbiology)
IntroductionExposure to heavy metals is a growing environmental concern. Although exposure to individual metals is associated with pulmonary damage, real-world exposure typically involves multiple metals simultaneously. This study hypothesizes that combined exposure to nickel, copper, and arsenic induces lung injury through disruption of the bronchoalveolar lavage fluid (BALF) microbial ecosystem in rats. The primary objective of this study was to verify the hypothesis.MethodsThirty-two male Sprague–Dawley (SD) rats were randomly assigned to four groups: one control group and three exposure groups (low, medium, and high doses). The exposed groups received mixed heavy metal aerosols containing nickel (Ni), copper (Cu), and arsenic (As) at low (Ni: 210.9 ng/m3, Cu: 108.4 ng/m3, As: 104.6 ng/m3), medium (5 × low), and high (10 × low) concentrations. Exposure occurred via inhalation twice daily for 1 h over 90 days. Lung function was assessed non-invasively, and histological examinations, 16S ribosomal DNA (16S rDNA) sequencing, and microbial functional predictions were performed to evaluate exposure effects. We measured heavy metal concentrations in lung tissues and assessed the associations with microbial changes. Microbial community structure and function were further analyzed using LEfSe, PICRUSt2, and ecological network analysis.ResultsCompared exposure to Ni, Cu, and As induced dose-dependent lung damage, including inflammation, alveolar deformation, and bronchial thickening, accompanied by significant declines in lung function, including a 21.2% reduction in tidal volume and a 34.5% increase in airway resistance in the high-dose group (P < 0.05). Microbial diversity and phylogenetic richness were significantly reduced (Chao1, Richness, ACE, P < 0.05), with taxonomic shifts characterized by the enrichment of metal-resistant genera (Pseudomonas, Burkholderia) and depletion of sensitive taxa (Ralstonia, Achromobacter). Functional prediction suggested impairments in xenobiotic metabolism and amino acid biosynthesis. Ecological network complexity declined with increasing exposure dose. Microbiota dysbiosis is strongly associated with lung function impairments.ConclusionsCombined exposure to Ni, Cu, and As disrupts respiratory microbiota and impairs lung function in rats. These findings highlight a critical link between environmental heavy metal exposure and respiratory health, underscoring the need for stricter regulation of metal pollutants and further research into microbiota-related lung injury mechanisms.